2011
DOI: 10.1111/j.1469-7998.2010.00763.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal gait parameters in the alpaca and the evolution of pacing and trotting locomotion in the Camelidae

Abstract: Alpacas are increasingly popular as domesticated companion and commercial animals. Their footfall patterns, however, are not well documented. It would be fascinating to know if artificial selection has changed alpacas' locomotor patterns from the ancestral condition in the vicu˜na. Some members of the Camelidae pace rather than trot, but the gaits of most species have not been studied quantitatively. Thus, investigating alpacas' gaits might contribute to understanding the factors influencing gait choice and ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 36 publications
1
26
0
1
Order By: Relevance
“…It has been suggested that this gait limits interference between limbs in animals with long limbs (Dagg, 1973). A study of alpacas found that these animals use lateral sequence walks at slow speeds (Fr >0.68; Pfau et al, 2011), which is similar to the results of our study despite the distinct evolutionary history and morphological differences between bears and alpacas. The trot and the pace require forelimbs and hindlimbs of equal length, with a straight short back (Dagg, 1973); bears are characterised as having a relatively long, sloping back and this may be limiting their use of these gaits.…”
Section: Gaitssupporting
confidence: 82%
“…It has been suggested that this gait limits interference between limbs in animals with long limbs (Dagg, 1973). A study of alpacas found that these animals use lateral sequence walks at slow speeds (Fr >0.68; Pfau et al, 2011), which is similar to the results of our study despite the distinct evolutionary history and morphological differences between bears and alpacas. The trot and the pace require forelimbs and hindlimbs of equal length, with a straight short back (Dagg, 1973); bears are characterised as having a relatively long, sloping back and this may be limiting their use of these gaits.…”
Section: Gaitssupporting
confidence: 82%
“…All the alpacas in this study were anecdotally found to be asymptomatic for pain and did not exhibit obvious clinical signs of pain or abnormality of gait or neck movement. Each alpaca was observed to have a symmetrical gait with a lateral sequence footfall pattern when walking that was assessed to be sound, clinically normal, and not suffering from any orthopedic disease . Several IVDs presented decreased MR signal intensity and had visible defects associated with the disc structure, including disc protrusions ( n = 9), disc prolapse ( n = 5), spinal cord impingement ( n = 1), and mild spinal cord deviation ( n = 3), as shown in Figure .…”
Section: Resultsmentioning
confidence: 99%
“…El canter es un movimiento semejante al galope, aunque relativamente más lento, en el que las extremidades anterior derecha/ posterior izquierda se mueven juntas en una fase (Webb, 1972;Collins y Stewart, 1993;Kienapfel et al, 2014). La velocidad promedio de los camélidos de Pie de Vaca es mayor en comparación a la velocidad promedio de una llama o una alpaca al caminar, la cual es de 1.13 m/s y 0.97 m/s respectivamente (Pfau et al, 2011;Kienapfel et al, 2014). Con base en esto, se propone que los camélidos que generaron los rastros de Pie de Vaca estaban realizando un caminar rápido similar al canter.…”
Section: Tamaño Velocidad Y Modo De Progresiónunclassified